2014
DOI: 10.1007/s10654-014-9887-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of Parkinson’s disease associated with lower body mass index and heavy leisure-time physical activity

Abstract: The risk factors for Parkinson's disease (PD) are not well established. We therefore examined the prediction of various lifestyle factors on the incidence of PD in a cohort drawn from the Finnish Mobile Clinic Health Examination Survey, conducted in 1973-1976. The study population comprised 6,715 men and women aged 50-79 years and free of PD at the baseline. All of the subjects completed a baseline health examination (including height and weight measurements) and a questionnaire providing information on leisur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 40 publications
6
72
2
Order By: Relevance
“…The shorter follow-up time was applied due to the suspicion that the prediction of single exposure measurement weakens in time. This Table 2 Baseline characteristics a suggestive result is in line with the hypothesis that obesity could be a risk factor for PD, supported by three prospective studies indicating increased PD risk for individuals with high BMI [11,13] or increased triceps skinfold thickness [9]. However, the epidemiologic literature on the association between BMI and PD risk is inconsistent [8,10,12].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The shorter follow-up time was applied due to the suspicion that the prediction of single exposure measurement weakens in time. This Table 2 Baseline characteristics a suggestive result is in line with the hypothesis that obesity could be a risk factor for PD, supported by three prospective studies indicating increased PD risk for individuals with high BMI [11,13] or increased triceps skinfold thickness [9]. However, the epidemiologic literature on the association between BMI and PD risk is inconsistent [8,10,12].…”
Section: Discussionsupporting
confidence: 75%
“…This inconsistency could be explained by the preclinical disease stage of PD masking the associations, since PD patients tend to lose weight during the disease progression, starting already several years before the clinical diagnosis [31]. Studies excluding the first 3e5 years of follow-up did not found an association between BMI and PD risk [8,10,12], whereas a recent finding from another Finnish cohort suggested an inverse association after exclusion of the first 15 years of follow-up [13]. The mechanism behind the association between obesity and the PD risk is poorly understood, but obese persons were found to have lower dopamine receptor availability than non-obese controls [32], which could predispose them to higher PD risk.…”
Section: Discussionmentioning
confidence: 98%
“…Our study with nearly 360 PD cases enrolled a substantially larger number of PD affected participants than most previous studies [10, 11, 24, 30]. Moreover, ours is the only epidemiologic population-based study in which movement disorder specialists examined 71% of patients multiple times over almost a decade to confirm a diagnosis of idiopathic PD, minimizing disease misclassification potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these cohort studies relied on self-report of physical activity levels or recorded activity patterns at baseline only [11, 12], accrued small numbers of incident PD cases or followed populations with a life-style different from the general population [10, 11]. In addition, most previous studies focused on leisure time activities while only two considered work related activities [8, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Humans participating in regular exercise programs exhibit brain volume increases in the supplementary motor area, right inferior frontal gyrus, left superior temporal gyrus, anterior cingulate, and hippocampus (Colcombe et al, 2006; Erickson et al, 2011). Being more physically active is also associated with reduced Alzheimer's (Lautenschlager et al, 2008) and Parkinson's (Saaksjarvi et al, 2014) disease risk. These are important findings because TBI is a risk factor for the accelerated onset and development of neurodegenerative diseases including Alzheimer's and Parkinson's (Jafari et al, 2013; Sivanandam and Thakur, 2012).…”
Section: Discussionmentioning
confidence: 99%